Defect engineering in semiconducting oxides: Control of ZnO surface potential via temperature and oxygen pressure. Issue 2 (21st September 2015) - Li, Ming; Seebauer, Edmund G.
Abstract : The technological usefulness of a semiconductor often depends on the types, concentrations, charges, spatial distributions, and mobilities of the atomic‐scale defects it contains. For semiconducting metal oxides, defect engineering is relatively new and involves complex transport and reaction networks. Surface‐based methods hold special promise in nanostructures where surface‐to‐volume ratios are high. This work uses photoreflectance augmented by X‐ray photoelectron spectroscopy to show that the surface potential V S for Zn‐terminated ZnO(0001) can be manipulated over a significant range 54.97–79.08 kJ/mol (0.57–0.82 eV) via temperature and the partial pressure of O2 . A defect transport model implies this variation in V S should affect the injection rate of oxygen interstitials by a factor of three. Such injection plays an important role in controlling the concentrations of oxygen vacancies deep in the bulk, which often prove troublesome as trapping centers in photocatalysis and photovoltaics and as parasitic emitters in light‐emitting devices. © 2015 American Institute of Chemical Engineers AIChE J, 62: 500–507, 2016